Pengaruh Sertifikasi Halal Terhadap Kesetiaan Konsumen Pada Produk Makanan dan Minuman: Studi Kasus Konsumen Non-Muslim di Daerah Istimewa Yogyakarta - Agus Susetyohadi; Mufti Alam Adha; Afrilia Dwi Utami; Dwi Esti Sekar Rini (ITB AAS INDONESIA Surakarta, 2021)
Indonesia is serious about positioning itself as the world's halal center and a pioneer in halal certification globalization. The public as consumers also has the right to get correct information about the halal-certified food products they need. It's related to consumers' safety both Muslim and non-Muslim, both in faith, spiritually and physically, in consuming food and beverage products. It is very dependent on information on these food products. The Government's efforts related to food products that are Halal certified in the community are by issuing Law no. 33 of 2014 concerning Halal Product Guarantee, which will be enforced three years later as a transition period. Many things influence consumer loyalty to a product. Among them, product quality, price, design, promotion, brand ambassador. Consumers will have high loyalty to a product if the product is of high quality. In other words, the product can provide the satisfaction expected by consumers. Samples were taken randomly according to the criteria set by the researcher. The data analysis technique used Structural Equation Modeling (SEM). This study used 185 responses from respondents, which were obtained using a google form survey. This study indicates that the variables of product quality, price, design, promotion, and brand ambassador have a significant positive effect on consumer loyalty to halal-certified products. It shows that halal certification for non-Muslim consumers is also one factor that needs to be considered and taken into consideration for food and beverage product producers.